26.6k views
3 votes
Solve for c . a(b-c) = d

User Anyah
by
6.1k points

1 Answer

5 votes

Answer:


c=(ab-d)/(a)

Explanation:

So we are given the equation:

a(b - c) = d

and we are asked to solve for c. To solve for c, we much get the c by itself on one side of the equation and all of the non-c components on the other side.

a(b - c) = d

Distribute the a on the left side of the equation.

ab - ac = d

Subtract ab from both sides of the equation.

-ac = d - ab

Divide both sides of the equation by -a.


c=(ab-d)/(a)

And now we have solved for c.

I hope you find my answer and explanation to be helpful. Happy studying.

User Atif
by
4.9k points